2022
DOI: 10.1177/17534666221113663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between high-flow nasal cannula and noninvasive ventilation in COVID-19 patients: a systematic review and meta-analysis

Abstract: Background: High-flow nasal cannula (HFNC) and noninvasive ventilation (NIV) are important treatment approaches for acute hypoxemic respiratory failure (AHRF) in coronavirus disease 2019 (COVID-19) patients. However, the differential impact of HFNC versus NIV on clinical outcomes of COVID-19 is uncertain. Objectives: We assessed the effects of HFNC versus NIV (interface or mode) on clinical outcomes of COVID-19. Methods: We searched PubMed, EMBASE, Web of Science, Scopus, MedRxiv, and BioRxiv for randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
(232 reference statements)
1
12
0
Order By: Relevance
“…However, the study findings may not be generalizable to moderate to severe COVID-19 patients, as the mean FiO 2 used was 38%, suggestive of milder COVID illness. Recently, a systematic review and meta-analysis by Yun Peng et al [19], including 3 RCTs and 20 observational studies comparing the use of NIV versus HFNC in both ICU and ward patients, demonstrated no difference in mortality rate between helmet NIV and HFNC, confirming the findings of our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, the study findings may not be generalizable to moderate to severe COVID-19 patients, as the mean FiO 2 used was 38%, suggestive of milder COVID illness. Recently, a systematic review and meta-analysis by Yun Peng et al [19], including 3 RCTs and 20 observational studies comparing the use of NIV versus HFNC in both ICU and ward patients, demonstrated no difference in mortality rate between helmet NIV and HFNC, confirming the findings of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the meta-analysis showed no statistically significant differences in the PaO 2 /FiO 2 ratio, total number of hospital or ICU days, and intubation rate between the HFNO and NIV groups. 36 A literature review of patients with COVID-19 revealed that HFNO can decrease the need for intubation, the severity of complications related to mechanical ventilation, and the duration of ICU stay. 37 A clinical study of 1400 patients showed that the 60-day risk of mortality was similar between patients who had received invasive mechanical ventilation since admission and patients those intubated after NIV.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our search revealed that HFNO/ APP strategy can avoid or delay intubation in patients at risk, but intubation remains a clinicians’ decision based on individual patients’ factors (i.e., tiring, work of breathing, consolidation burden). The use of HFNO alone demonstrated lower intubation rates both in patients with and without COVID-19 AHRF ( Agarwal et al, 2020 , Demoule et al, 2020 , Ospina-Tascón et al, 2021 , Peng et al, 2022 , Perkins et al, 2022 ) . Additionally, HFNO facilitates the management of FiO 2 reliably while concurrently modifying the conditions of the gas supplied such as temperature and humidity ( Raoof et al, 2020 , Suffredini and Allison, 2021 ).…”
Section: Discussionmentioning
confidence: 99%